Wolfgang Beck, Ohne Geländer. Pastoraltheologische Fundierungen einer risikofreudigen Ekklesiogenese - Frey, Regina Maria (Münchener theologische Zeitschrift, 2025)
The article discusses Wolfgang Beck's habilitation thesis, which engages with the thesis of a risk-taking pastoral theology. The book is divided into three parts: the first part addresses modern approaches to risk, the second part examines the church's willingness to take risks throughout history and in the present, while the third part highlights Christianity and its willingness to take risks in pastoral and theological contexts. Beck argues for an open and context-sensitive pastoral theology that is oriented towards risk theories from various disciplines. Despite the comprehensive analysis, occasional superficialities and ambiguities in theological terminology are noted.